Tingkat Kesukaan Terhadap Minuman Loloh Don Piduh Melalui Uji Organoleptik - Putu Mira Astuti Pranadewi (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The herbal drink loloh don piduh is one of the traditional Balinese drinks that can be enjoyed by all ages and groups Loloh don piduh itself is made from processed don piduh or with the Latin name (Centella Asiatica). With tons of benefits and a sweet, refreshing taste, loloh don piduh has great potential in the market. The large potential to be developed, its necessary to carry out the organoleptic test to assess the level of the preference of the panellist. Therefore this research was conducted to determine the level of consumer preference for the herbal drink loloh don piduh through an organoleptic test which was attended by 15 panelists, using questioner with 7 hedonic scales and 5 indicators namely color, aroma, sweetness, acidity, and bitterness. The results of the organoleptic test identified that all the panellist rated like of colour, aroma, acidity, and bitterness indicators. And the panellist rated very like of the sweetness indicator of loloh don piduh. The final results of this research that the loloh don piduh herbal drink can be accepted by consumers, connoisseurs and industry players. And this drink deserves to be introduced to the wider community in Bali and foreign tourists